PENERAPAN NILAI-NILAI HUKUM EKONOMI ISLAM PADA PRODUK-PRODUK PERBANKAN SYARIAH (STUDI PADA BANK BNI SYARIAH CABANG PANGKEP) - Rahmatullah, Nursalam (Fakultas Syariah IAI Muhammadiyah Bima, 2020)
The Implementation of Islamic Economic Law Values ​​on the Products of BNI Sharia of Pangkep Branch which Includes, 1) Amar ma’rūf nahyi munkar, 2) Ta’āwun, 3) Justice, 4) Not usury, 5) Not garar in getting treasure has not been optimally implemented considering there is still element of garar in micro finance products where the bank as a seller selling an object of goods that have not owned. It was happened due to several factors such as: 1. The fulfillment of hard-to-reach annual targets, 2. The dishonest and closed clients concerning the proposed financing purposes, 3. The clients demanding liquidation as soon as possible, and 4. The employees of BNI Sharia of Pangkep Branch particularly did not understand the nature and legal consequences of sale and purchase of garar coupled with the lack of customers’ understanding related to murabahah bi al-wakalah so that the process of financing with a predetermined flow cannot be executed according to the rules in force.